Factores Psicosociales de Riesgo que Inciden en la Salud Bucal de población del Adulto Mayor (2021)
The promotion and prevention in the elderly population is essential because the regenerative capacity of the body decreases due to the age, at this stage of life there is a process of wear and tear in which chronic diseases occur. Likewise, there are oral manifestations typical of the age or the systemic condition of each individual, for this reason, alterations of the oral cavity can limit the performance of daily activities and the psychosocial impact of these oral problems can impair the style life of individuals.